Concordance between self-reported and measured HIV and hepatitis C virus infection status among people who inject drugs in Germany. Issue 1 (December 2016) - Nielsen, Stine; Gassowski, Martyna; Wenz, Benjamin; Bannert, Norbert; Bock, Claus-Thomas; Kücherer, Claudia; Ross, R.; Bremer, Viviane; Marcus, Ulrich; Zimmermann, Ruth
Abstract Background People who inject drugs (PWID) are disproportionately affected by both HIV and hepatitis C infection (HCV). Awareness of infection status is essential to ensure linkage to appropriate healthcare for those infected, who need treatment and regular follow-up, as well as for uninfected individuals, who need access to targeted testing and counselling services. In this paper we compare self-reported HIV and HCV status with serological markers of infection among PWID recruited through respondent driven sampling. Methods From 2011 through 2014, biological and behavioural data was collected from 2, 077 PWID in Germany. Dried blood spots from capillary blood samples were collected and screened for HCV antibodies, HCV RNA and HIV-1/-2 antibodies. HIV reactive samples were confirmed by Western blot. Results Laboratory testing revealed that 5 % were infected with HIV and 81 % were aware of being infected. Chronic HCV infection was detected in 41 % of the participants, 2 % had an acute HCV infection, 22 % had a cleared infection, and 34 % were unexposed to HCV. The concordance between self-reported and measured HCV status was lower than for HIV, with 73 % of those with chronic HCV infection being aware of their infection. Conclusions We found a relatively high awareness of HIV and HCV infection status among PWID. Nevertheless, access to appropriate testing, counselling and care services targeted to the needs of PWID should be further improved, particularly concerning HCV. Trial registration Ethical approval was received from the ethics committee at the medical university of Charité, Berlin, Germany in May 2011 and with an amendment approved retrospectively on 19/11/2012 (No EA4/036/11). The German Federal Commissioner for Data Protection and Freedom of Information approved the study protocol retrospectively on 29/11/2012 (III-401/008#0035).